SURVEI TINGKAT PENGETAHUAN DAN SIKAP TENTANG ASI EKSKLUSIF PADA PESERTA KOLOMPOK PENDUKUNG IBU (KP-IBU) - Asmarani, Hani; Tyastuti, Siti; Maryani, Tri (Poltekkes Kemenkes Yogyakarta, 2015)
Based on the WHO study in 6 developing countries, the risk of death among infants aged 9-12 months increased by 40% and infants under 2 months of age increased to 48% if not breastfed (Roesli, 2008). National Socio-Economic Survey of 2O10 showed coverage of exclusive breastfeeding in Indonesia 33.6% (the national target of 80%). Coverage of exclusive breastfeeding in DIY reached 49.5%. Whereas in Bantul Regency showed a decrease of 42.34% (in 2011) to 39% (in 2012) (Bantul Health Office, 2012). Bantul government since 2009 has launched a program of Mother Support Group to improve the knowledge, attitudes, and practices of exclusive breastfeeding. Objective purpose to know the level of knowledge and attitude about exclusive breastfeeding on participants in the Mother Support Group at the working area Public Health Center Banguntapan ll. The method this type of study isa descriptive survey to describe the knowledge and attitudes of participants Mother Support Group about exclusive breastfeeding. The subjects were all women attending Mother Support Group who has babies aged 0-6 months as many as 81 people. instruments this study in the form of questionnaires. Data analysis using descriptive statistics. The majority knowledge level of the participant's mother support group about exclusively breastfeeding in good category (76.54%) and the attitude of the participants Mother Support Group is majority supportive (82,720/,) for exclusive breastfeeding. The participant's Mother Support Group has good knowledge about exclusive breastfeeding and supportive attitude towards exclusive  breastfeeding.